Epigenetic regulation of bladder cancer in the context of aging - Xuewei Liu; Guofeng Ding; Yifan Liu; Xiaoli Yan; Yan Zhao; Hailin Lv; Xiaojuan Xu (Frontiers in Pharmacology)
Bladder cancer (BC) is a disease that predominantly affects older adults, with aging playing a critical role in its onset and progression. Age-associated phenomena, including immunosenescence and chronic inflammation, form a pro-tumor milieu, while genomic instability and epigenetic drift further increase cancer risk. The review highlights the dual role of DNA methylation in BC: global hypomethylation can activate transposable elements and oncogenes, whereas focal hypermethylation silences tumor-suppressor genes like CDKN2A, especially detrimental in older tissues that rely on these genes for senescence control. In parallel, frequent mutations in chromatin modifiers (e.g., KDM6A, KMT2D) and overexpression of histone-modifying enzymes (e.g., EZH2) alter the tumor epigenome to promote immune evasion and tumor aggressiveness. At the non-coding RNA level, dysregulated microRNAs (miRNAs) and long non-coding RNAs (lncRNAs) in BC contribute to aberrant proliferation, metastatic potential, and immune suppression, with aging-associated declines in miRNA processing further exacerbating these effects. Collectively, the accumulation of epigenetic alterations in older patients appears to facilitate both tumor progression and resistance to therapy. Looking forward, epigenetic biomarkers may improve early detection and risk stratification. Furthermore, “epigenetic therapies,” such as DNA methyltransferase inhibitors (DNMTi), EZH2 inhibitors (EZH2i), or histone deacetylases inhibitors (HDACi), hold promise to restore tumor-suppressor function and enhance immunogenicity, offering an attractive avenue for improving outcomes in older patients with BC.